2014
DOI: 10.1017/s0022215114000450
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary function in patients with chronic rhinosinusitis and allergic rhinitis

Abstract: The findings indicated latent obstructive lung function changes in chronic rhinosinusitis patients. The cytokines in nasal secretions might be related to obstructive lung function changes in chronic rhinosinusitis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
26
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(28 citation statements)
references
References 34 publications
2
26
0
Order By: Relevance
“…In addition, the levels of IL-5 in nasal secretion in the middle meatus were significantly correlated with lung function changes. 75 We have also demonstrated in another study that obstructive lung dysfunction was more impaired in non-asthmatic patients with CRSwNP with peripheral blood eosinophilia (eosinophil percentage to total leukocyte equal or more than 5%) than in those without eosinophilia, especially in elderly patients aged 60 years old or more. 76 Similar explanations as those put forward to account for the relationship between AR and asthma have been proposed to explain why the presence of CRS induces lower airway inflammation and dysfunction.…”
Section: Presence and Characterization Of Comorbidity Of Chronic Rhinsupporting
confidence: 52%
“…In addition, the levels of IL-5 in nasal secretion in the middle meatus were significantly correlated with lung function changes. 75 We have also demonstrated in another study that obstructive lung dysfunction was more impaired in non-asthmatic patients with CRSwNP with peripheral blood eosinophilia (eosinophil percentage to total leukocyte equal or more than 5%) than in those without eosinophilia, especially in elderly patients aged 60 years old or more. 76 Similar explanations as those put forward to account for the relationship between AR and asthma have been proposed to explain why the presence of CRS induces lower airway inflammation and dysfunction.…”
Section: Presence and Characterization Of Comorbidity Of Chronic Rhinsupporting
confidence: 52%
“…It may be explained by only anatomical changes in septal deviation to anatomical as well as physiological changes in the respiratory mucosa occurring in chronic rhinosinusitis. In a study by Kariya et al 6 pulmonary function was measured in 68 (23.2%) patients with chronic rhinosinusitis without nasal polyps, 89 (30.4%) patients with allergic rhinitis, 135 (46.2%) patients with chronic rhinosinusitis with nasal polyps and 100 normal controls. They found that pulmonary function of patients with chronic rhinosinusitis was significantly affected thus indicating latent obstructive lung function changes in chronic rhinosinusitis patients which supported our findings.…”
Section: Discussionmentioning
confidence: 99%
“…Long-term inflammatory stimulation of the bronchus causes the formation of chronic inflammation and small airway abnormality, then leading to declined pulmonary ventilation and small airway obstruction. Kariya et al [17] found the level of interleukin-5 in nasal secretions was significantly correlated with pulmonary function in patients with CRS. These studies indicate or suggest CRS patients will suffer from impairments of lung function.…”
Section: Discussionmentioning
confidence: 99%